PERBANDINGAN HASIL BELAJAR FISIKA SISWA KELAS XI YANG MENGGUNAKAN METODE PEMBELAJARAN PETA PIKIRAN (MIND MAPPING) DAN METODE PEMBELAJARAN PETA KONSEP (CONCEPT MAPPING) - Dwi Wahyu Ningrum; Siswoyo Siswoyo; Cecep E. Rustana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The purpose of this research is to know the different of physics’s learning outcomes of students using mind mapping learning method and concept mapping learning method. The research is conducted in SMAN 30 Jakarta school year 2014/2015. The method used in this research is quacy experiment with Posttest Only Comparison Group Design. The sampling technique used purposive sampling with the sample are XI-MIA1 as experiment class1 and XI-MIA 2 as experiment class 2. The instrument of this research is multiple choice formed with 25 questionares. Requirement test uses normality test with Liliefors since Lo(0,0924)<Ltable(0,1477) on experiment class 1 and Lo(0,1311)<Ltable(0,1497) on experiment class 2, that shown population is distributed normal. On homogenity test for α= 5%  and df1=34; df2=35 obtained Fcount(1,489)Ftable(1,76), therefore the data obtained are homogeneous. Data of the result in this research is analized using t-test with pooled varian formula. Based on hypothesis test, shown that tcount(2,35) and ttable(1,667) at significance level α= 5% with dk= 36+35-2= 69. Because of tcount>ttable, then H0 is rejected and Ha is accepted. So it can be concluded that that physics’s leraning outcomes on mind map learning method higher than the results of physics’s learning outcomes on concept map learning method.Keywords: mind mapping, concept mapping, physics’s learning outcomes.